2012
DOI: 10.1126/scisignal.2002299
|View full text |Cite
|
Sign up to set email alerts
|

Direct Binding Between Orai1 and AC8 Mediates Dynamic Interplay Between Ca 2+ and cAMP Signaling

Abstract: A signaling complex enables the compartmentalized regulation of cyclic AMP signaling by calcium entering through a specific channel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
119
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(131 citation statements)
references
References 55 publications
7
119
0
Order By: Relevance
“…In wild-type HEK293 cells SOCE has no effect on cAMP production due to the absence of Ca 2+ -stimulated AC isoforms, confirming a dependence of Ca 2+ -stimulated cAMP production in HEK-AC8 cells on the overexpression of the Ca 2+ -stimulated AC isoform (Willoughby et al, 2012). Under the same experimental conditions HEK-AC8 cells overexpressing AKAP79-HA displayed reduced Ca 2+ -dependent cAMP production ( Fig.…”
Section: Akap79-targeted Pka Regulates Ac8 5851supporting
confidence: 63%
See 1 more Smart Citation
“…In wild-type HEK293 cells SOCE has no effect on cAMP production due to the absence of Ca 2+ -stimulated AC isoforms, confirming a dependence of Ca 2+ -stimulated cAMP production in HEK-AC8 cells on the overexpression of the Ca 2+ -stimulated AC isoform (Willoughby et al, 2012). Under the same experimental conditions HEK-AC8 cells overexpressing AKAP79-HA displayed reduced Ca 2+ -dependent cAMP production ( Fig.…”
Section: Akap79-targeted Pka Regulates Ac8 5851supporting
confidence: 63%
“…Growing evidence shows that ACs can function as central components of macromolecular signalling complexes targeted to specific receptors or ion channels, where they are exposed to the highly localised activities of other scaffolded signalling molecules that function downstream of cAMP (Dessauer, 2009;Willoughby et al, 2012). AKAP79/150 is a prototypical AKAP in that it contains an amphipathic a-helix that binds PKA RII subunits, it also can be targeted to discrete regions of the cell, and can interact with multiple signalling molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated a direct protein interaction between Ca 2+ -CaM activated AC8 and Orai1 N terminus (Willoughby et al, 2012). Using Forster resonance energy transfer (FRET) technique, GST pulldown, and immunoprecipitation analyses, the authors detected a constitutive association between Orai1 and AC8, which was not affected by store depletion and Orai1 activation (Willoughby et al, 2012). Both these studies together show that STIM1 itself or Ca 2+ entry via Orai1 plays an integral role in regulating crosstalk between SOCE and cAMP signaling pathways.…”
Section: +mentioning
confidence: 80%
“…It was shown that intracellular store depletion, independent of cytosolic Ca 2+ concentration, led to recruitment of ACs in a STIM1-dependent mechanism referred by the authors as "store-operated cAMP signalling". Another study demonstrated a direct protein interaction between Ca 2+ -CaM activated AC8 and Orai1 N terminus (Willoughby et al, 2012). Using Forster resonance energy transfer (FRET) technique, GST pulldown, and immunoprecipitation analyses, the authors detected a constitutive association between Orai1 and AC8, which was not affected by store depletion and Orai1 activation (Willoughby et al, 2012).…”
Section: +mentioning
confidence: 99%
“…The shorter form of Orai1 (Orai1␤) originates from an alternative initiation-translation of the Orai1 mRNA at methionine 63 (M63; blue) (17,26). Orai1 contains a region shown to mediate interaction with the Ca 2ϩ -sensitive adenylate cylase 8 (AC8; green line) (98), which contains 2 serine residues (S27 and S30; green), which are targets for phosphorylation by protein kinase C (34), and a putative caveolin-binding domain (purple line). Orai2, the smallest of the 3 isoforms, contains all conserved functional domains, with its CaM-binding domain spanning H42-R65, its pore-selectivity filter residue at E80, and its COOH-terminal coiled-coil domain spanning residues S221-Q252.…”
Section: Orai Proteins In Smooth Musclementioning
confidence: 99%